Wet-Chemical Approaches for Atomic Layer Etching of Semiconductors: Surface Chemistry, Oxide Removal and Reoxidation of InAs (100). (1st January 2015) - van Dorp, Dennis H.; Arnauts, Sophia; Holsteyns, Frank; De Gendt, Stefan
Abstract : An approach for wet-chemical atomic layer etching (WALE) of semiconductors is described. The surface chemistry of InAs was investigated for HCl/H2 O2 solutions suitable for controlled etching in the low etch rate range (<0.1–10 nm min −1 ). Kinetic studies were performed using inductively coupled plasma – mass spectrometry (ICP-MS). As for GaAs and InGaAs, the importance of the Cl − ion for the etching kinetics is demonstrated and a chemical reaction scheme is presented to help understand the surface chemistry. A detailed study of an alternative two-step etching process was performed. A quantitative ICP-MS analysis of the oxide formed in O3 /H2 O solution and the dissolution in HCl was performed suggesting that the removal of oxidized In products is the slow step in the dissolution reaction. The reoxidation of oxide-free InAs (100) surfaces in air is discussed. The etch rate range and the surface morphology control after etching show that the investigated wet-chemical approach for atomic-layer etching is a valid candidate for advanced CMOS processing.